Interference with orco gene expression affects host recognition in Diorhabda tarsalis - Chen, Hong-Hao; Dewer, Youssef; Wang, Yan; Tan, Shu-Qian; Liu, Xiao-Li; Shi, Wang-Peng (Frontiers in Physiology, 2022)
Diorhabda tarsalis Weise is an important insect pest of the Chinese licorice Glycyrrhiza uralensis Fisch. The volatiles pest-induced from the plant showed more attractive to D. tarsalis. Through sequencing analysis, 29 odorant receptor candidate genes of D. tarsalis were obtained, which code for 130–479 amino acids. Phylogenetic trees of olfactory receptors were constructed with 243 ORs from eight Coleoptera species. DtarORco, DtarOR7 and DtarOR26 are specifically expressed in the antenna, and the expression levels were significantly higher than other DtarORs in antenna, there were no differential expression between male and female beetles. An odorant coreceptor gene (DtarORco) has characteristics of an odorant receptor family member, the encoded mature protein has a predicted molecular weight of 53.898 kDa, dsRNA L4440 expression vectors were constructed and successfully transformed into ribonuclease III-deficient Escherichia coli strain HT115 DE3. After interference treatment, the relative expression level of DtarORco in D. tarsalis antennae significantly decreased and electrophysiological responses to host localization odor signals significantly decreased. At the same time, beetles lost the ability to locate hosts. The research on its mechanism of olfaction may lead to the development of new control measures that are environmentally friendly.